Development of Online Facilities Booking System - Tan, Yi Yein (2003)
The purpose of this project is to develop an online system that manages company resources by using web technology. By using this system, the author hopes to reduce the workload of employees, cut the cost of resources and people and enable the booking of resources to be done quickly. The system is operated in Windows environment and supported by IIS or PWS web server and Microsoft Access database. VB Script and Java Script with ASP of server side technology are used to write the whole system. As this system is web-based, employees can access to this system at anytime and any place that have internet access. Bookings done are easily to monitor and track from the Bookings Calendar